Primary Pulmonary Synovial Sarcoma in Pregnancy - Bunch, K. (Hindawi Publishing Corporation, 2012)
Background. Primary pulmonary synovial sarcoma is a rare malignancy with a poor prognosis. Surgical resection and postoperative management of these tumors has not been previously described in pregnancy. Case. A 38-year-old pregnant woman was admitted for evaluation of a right thoracic mass found on chest radiography at 26 weeks of gestation. A computed tomography-guided biopsy was subsequently completed and demonstrated a high-grade neoplasm. A right pneumonectomy was performed at 28 weeks of gestation due to pulmonary decompensation, and pathological examination revealed a pulmonary synovial sarcoma. The patient developed a postpartum pulmonary embolism and expired 6 weeks after delivery. Conclusion. Aggressive intervention for pulmonary malignancies during pregnancy may be necessary. Complete tumor resection is the most important prognostic factor in primary pulmonary synovial sarcoma.